An 8-week physical exercise intervention for e'athletes improves physical performance rather than short-term esports performance parameters - a randomized controlled trial - Wachholz, Felix; Gamper, Nicole; Schnitzer, Martin (Frontiers in Sports and Active Living, 2025)
IntroductionEsports have been suggested to enhance hand-eye coordination, fine motor skills, and reaction times. While physical exercise is known to improve these abilities, its impact on short-term esports performance is under-researched. This study aims to evaluate the effects of specific and general physical training on gaming performance, hypothesizing improvements in both physical and gaming-related variables.MethodsBaseline and follow-up tests measured global coordination, grip strength, Aimlabs performance, single and 4-fold reaction times, and anticipation. Participants completed a weekly and an ending questionnaire. Twenty-eight participants (12.3 ± 10.1 h gaming/week) were assigned to specific (N = 10), general (N = 9), and no training (N = 9) groups for an 8-week intervention. Variable changes over time and between groups were analyzed using a repeated measures ANCOVA.ResultsTraining significantly improved the overall coordination of those participants engaging in physical training compared to the control group [F(2,25) = 3.858, p = 0.035, η2 = 0.236]. Grip strength also showed significant improvement [F(2,25) = 6.084, p = 0.007, η2 = 0.327]. There were no significant time or group effects for the gaming variables, but the hours played by participants positively influenced Grid Shot [F(1,24) = 4.746, p = 0.039, η2 = 0.165] and Track Point [F(1,24) = 9.613, p = 0.005, η2 = 0.286] performance. The weekly questionnaire indicated a significant improvement in participants' well-being.DiscussionWhile training improved physical variables, no effects were observed in suggested short-term performance. However, gaming hours and experience during the intervention positively influenced performance. Future research should consider the amount of time spent playing as it may affect short-term performance. Furthermore, future research should strive to differentiate between various types of esports performance, such as short-term vs. long-term outcomes. Participants reported that engaging in physical activity within the context of esports and gaming positively contributed to their overall well-being. Clinical Trial RegistrationClinicalTrials.gov, identifier (NCT06264375).